What are the success factors for a partnership with global medical device companies? Evidence from Korea - Dongwoo Kim; Gyu Ha Ryu; Kwangsoo Shin; Kyu-Sung Lee (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The medical device industry is uniquely characterized by both resourceful global companies and innovative catching-up companies. The studies by Chatterji have analyzed how large and established medical device companies could better utilize the ideas from innovative groups such as physicians. While the existing literature on the topic of open innovation is enriched, there are few studies on the partnership between larger global medical device companies and smaller catching-up medical device companies. This study focuses on a structured partnership with global medical device companies. To understand how such a deal could be better arranged, this study adopted the Analytic Hierarchy Process (hereafter, AHP) analysis to derive the success factors of such partnership with a focus on the case of the Korean medical device industry. This survey interviewed 30 experienced professionals who currently work for global medical device companies. The study results found that global medical device companies prefer a licensing deal along with broader territories. In terms of the preferred requirements for a partnership deal, the study revealed that there is strong emphasis on factors such as Quality and Intellectual Property (hereafter, IP) protection. This study has practical managerial implications for catching-up medical device companies which drive an open innovation practice with a view to accelerating their growth trajectory in the global market.
Keywords: 650; open innovation; analytical hierarchy process; global partnership; medical device industry